국내산 참나무속 수종 잎의 추출성분 - 김진규; Jin Kyu Kim; 배영수; Young Soo Bae (목재공학, 2006)
This study was carried out to investigate chemotaxonomical correlation an d the chemical constituents of domestic Quercus sp. leaves. The leaves of Q. mongolica, Q. aliena, Q. serrata, Q. acutissima, Q. dentata and Q. variabilis were collected in the experimental forest of Kangwon National University. The combined extracts were successively fractionated with n -hexane, methylene chloride and ethyl acetate using a separation funnel. A portion of the ethyl acetate and $H_2O$ soluble materials of each species were chromatographed on a Sephadex LH-20 column using various aqueous MeOH and EtOH-hexane as washing solvents. Spectrometric analysis such as NMR and MS, including TLC, were performed to characterize the structures of the isolated compounds. Gallic acid, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, kaempferol, astragalin, astragalin-6"-O-gallate, isoquercitrin, isoquercitrin-6"-O-gallate and myricetin were isolated from Q. mongolic a leaves. Gallic acid, kaempferol and quercetin were characterized from Q. acutissima leaves. Gallic acid, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, (-)-epigallocatechin, kaempferol, quercetin, guajaverin and tamarixin were identified from Q. dentata leaves. Gallic acid, (+)-catechin, (-)-epicatechin, kaempferol, quercitrin, isoquercitrin and myricetin were purified from Q. serrata leaves. Gallic acid, (+)-catechin, astragalin, astragalin-6"-O-gallate and isoquercitrin were isolated from Q. variabilis leaves. Gallic acid was isolated from all the leaves and could be a taxonomic index on Quercus spp.. 국내산 주요 참나무류인 신갈나무, 상수리나무, 떡갈나무, 졸참나무, 갈참나무 및 상수리나무 잎의 추출성분의 구조를 규명하고 수종 상호간의 성분의 특성 및 상호 연관성 등을 조사하였다. 신갈나무에서는 gallic acid, (+)-catechin, (-)-epicatechin, (+)-gallocatechin, kaempferol, a stragalin, astragalin-6"-O-gallate, isoquercirin, isoquercitrin-6"-O-gallate 및 myricetin 등 10종의 화합물이 단리되었고 상수리나무에서는 gallic acid, kaempferol과 quercetin이 떡갈나무에서는 gallic acid, (+)-catechin, (-)-epicatechin, (+)-galocatechin, (-)-epigallocatechin, kaempferol, quercetin, guajaverin 및 tamarixin 등 9종의 화합물이 단리되었으며 갈참나무에서는 gallic acid, caffeic acid, astragalin, quercetin과 isoquercitrin이 졸참나무에서는 gallic acid, (+)-catechin, (-)-epicatechin, kaempferol, quercitrin, isoquercitrin 및 myricetin 등 7종의 화합물이 단리되었고 굴참나무에서는 gallic acid, (+)-catechin, astragalin, astagalin-6"-O-gallate와 isoquercitrin 등 5종의 화합물이 단리되었다. Gallic aicd는 모든 수종에서 단리되어 참나무류 잎 추출성분의 지표 화합물로 이용될 수 있다.